2013
DOI: 10.5539/elt.v6n7p88
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service English Teachers’ Beliefs on Speaking Skill Based on Motivational Orientations

Abstract: This study aimed to explore pre-service English teachers' perceptions of teaching speaking in Turkey, the importance they give to this language skill, and their self-evaluation of their speaking competence. With case design and maximum variation sampling approach, seven pre-service English teachers' beliefs about speaking skills were gathered in regard to motivational orientations based on Self-determination theory (Deci & Ryan 2002) and the data was analyzed according to interview questions. Findings revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…These findings are compatible with Dincer and Yesilyurt (2013) and Rabab'ah (2013 The results are supported by the findings of Adayleh (2013). The Iranian students of government schools learn English language in an educational milieu in which demotivation factors abound.…”
Section: Resultssupporting
confidence: 82%
“…These findings are compatible with Dincer and Yesilyurt (2013) and Rabab'ah (2013 The results are supported by the findings of Adayleh (2013). The Iranian students of government schools learn English language in an educational milieu in which demotivation factors abound.…”
Section: Resultssupporting
confidence: 82%
“…The analysis of the data revealed that the research lesson was slightly beyond students' level and was more grammar-oriented rather than communication-oriented. The fact that grammar teaching dominates over communication-oriented teaching in different educational levels in the Turkish EFL context has also been highlighted by many researchers (Tercanlıoğlu, 2004;Kırkgöz, 2007;Şad, 2010;Dinçer & Yeşilyurt, 2013;Uysal & Bardakçı, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ali Dincer & Savas Yesilyurt (2013) in their study Pre-Service English Teachers' Beliefs on Speaking Skills Based on Motivational Orientations showed that the findings revealed that "the subjects, whether they were intrinsically or extrinsically motivated to speak English, had negative ideas about speaking instruction in Turkey, though they all agreed that it was the most important language skill. The findings also showed that they felt incompetent in oral communication though they had different motivational orientations about speaking English.…”
Section: Previous Studies Related To Instructorsmentioning
confidence: 99%